Quality in forage of natural pasture under alternative managements - Heringer, Ingrid; Jacques, Aino Victor Ávila (Pesquisa Agropecuaria Brasileira, 2002)
Burning of native pasture affects soil, botanical composition, species development, and forage quality. It was studied five management systems of native pasture under grazing condition: biennial burning for more than 100 years; without burning for 32 years with or without mowing; and pasture improvement for 7 and 24 years. The experimental design was a completely randomized one, with three replications. Crude protein and in vitro organic matter digestibility were greater in improved and mowed areas. The level of N did not differ among treatments, while the levels of P, K, Ca and Mg were greater in improved area as compared to other treatments. The tissue nutrient quantity accumulated, as result of forage production, was greater in the systems without burning.